Impact of nanoparticles on plant physiology, nutrition, and toxicity: A short review - Devendra Singh; Avinash Sharma; Sunil Kumar Verma; Himanshu Pandey; Minakshi Pandey (Next Nanotechnology)
Due to the positive link between the application of nanoparticles (NPs) and the improved nutritional status/value of the plants exposed to them, nanomaterials have recently attracted rising interest in the field of agriculture. Numerous NPs, including carbon-based NPs, silica NPs, etc., have been discovered to positively affect plants by raising their ratio of nutrient uptake and nutrient utilization efficiency, amongst other things. All of these qualities have opened the door for potential improvements in plant development, vigor, growth, etc. when these NPs are used primarily as Nano fertilizers. In light of all of this, it is also possible to draw the conclusion that nanotechnology holds great promise for playing a significant role in the international situation of growing demand for the production of food as well as supply in the years to come. In order to give researchers working in this field a thorough understanding, an effort has been made to compile all the encouraging developments about the application of various NPs on plants, together with their likely mode of action, in this review.